Metabolite profiles of rats in repeated dose toxicological studies after oral and inhalative exposure. (25th July 2016) - Fabian, E.; Bordag, N.; Herold, M.; Kamp, H.; Krennrich, G.; Looser, R.; Ma-Hock, L.; Mellert, W.; Montoya, G.; Peter, E.; Prokudin, A.; Spitzer, M.; et al.
Highlights: Comparison of metabolic profiles in rat plasma after repeated inhalative and oral exposure for 6 toxicants with known toxicological mode of action. Route of exposure dependent metabolic response for toxicants with weak metabolome changes (low profile strengths) e.g. female rats dosed inhalatively with Aniline or Tetrahydrofurane. Route of exposure independent metabolic response for toxicants with profound metabolome changes (high profile strengths), e.g. rats dosed with chloroform or 2-methoxyethanol. Link of inhalatively tested compounds to MetaMap ® -Tox database with plasma-metabolome and toxicity data of rats for more than 550 reference compounds, dosed orally in an adapted OECD 407 protocol. Abstract: The MetaMap ® -Tox database contains plasma-metabolome and toxicity data of rats obtained from oral administration of 550 reference compounds following a standardized adapted OECD 407 protocol. Here, metabolic profiles for aniline (A), chloroform (CL), ethylbenzene (EB), 2-methoxyethanol (ME), N, N -dimethylformamide (DMF) and tetrahydrofurane (THF), dosed inhalatively for six hours/day, five days a week for 4 weeks were compared to oral dosing performed daily for 4 weeks. To investigate if the oral and inhalative metabolome would be comparable statistical analyses were performed. Best correlations for metabolome changes via both routes of exposure were observed for toxicants that induced profound metabolome changes. e.g. CL and ME. Liver and testes were correctly identified as target organs. In contrast, route of exposure dependent differences in metabolic profiles were noted for low profile strength e.g. female rats dosed inhalatively with A or THF. Taken together, the current investigations demonstrate that plasma metabolome changes are generally comparable for systemic effects after oral and inhalation exposure. Differences may result from kinetics and first pass effects. For compounds inducing only weak changes, the differences between both routes of exposure are visible in the metabolome.